Involvement of DNA methylation in regulating rat Prop1 gene expression during pituitary organogenesis - NISHIHARA, Hiroto; YOSHIDA, Saishu; KANNO, Naoko; NISHIMURA, Naoto; UEHARU, Hiroki; OHGANE, Jun; KATO, Takako; KATO, Yukio (Journal of Reproduction and Development, 2017)
PROP1 is a pituitary specific transcription factor that plays a crucial role in pituitary organogenesis. The Prop1 shows varied expression patterns that promptly emerge and then fade during the early embryonic period. However, the regulatory mechanisms governing Prop1 expression remain unclear. Here, we investigated whether Prop1 was under epigenetic regulation by DNA methylation. Bisulfite sequencing was performed on DNA obtained from the pituitary glands and livers of rats on embryonic days (E) 13.5 and E14.5, and postnatal days (P) 4 and P30. The methylation of CpG sites in seven regions from 3-kb upstream of the Prop1 transcription start site through to its second intron were examined. Certain differences in CpG-methylation levels were observed in Region-1 (–2772 b to –2355 b), Region-4 (–198 b to +286 b), Region-5 (+671 b to +990 b), and Region-6 (+1113 b to +1273 b) based on comparisons between pituitary and liver DNA on E13.5. DNA methylation in pituitary glands on E14.5, P4, and P30 was generally similar to that observed in in the pituitary gland on E13.5, whereas the anterior and intermediate lobes of the pituitary gland on P4 and P30 showed only small differences. These results indicate that Prop1 is under regulation by CpG methylation during the early period of pituitary primordium development around E13.5.